History of Indonesian Muslim Scholars and Other Religions Dialogue | تاريخ حوار علماء المسلمين الإندونيسيين والأديان الأخرى - Ghilmanul Wasath (Al-Zahra : Journal for Islamic and Arabic Studies, 2015)
This study discusses the history of religious dialogue in Indonesia, between Indonesian Muslim scholars and other religious leaders. Indonesian Muslim scholar involvement in religious dialogue is seen primarily in dialogue national level and international level. Results from this study reinforce the importance of inter-religious dialogue as a way of Islamic da'wah, humanitarian work, and to create religious harmony